2023
DOI: 10.15298/arthsel.32.1.08
|View full text |Cite
|
Sign up to set email alerts
|

A new jumping spider species of the genus Indopadilla Caleb et Sankaran, 2019 (Aranei: Salticidae) from the Central Highlands, Vietnam

Abstract: single sex only: i.e., five from the males and two from the females. To date, only one species, Indopadilla annamita (Simon, 1903) has been recorded from central Vietnam [Simon, 1903;Żabka, 1988; both sub Bavia].Recently, we performed several surveys of the spider fauna in the Chu Yang Sin National Park, Central Highlands, Vietnam and adjacent regions. As a result, a new jumping spider species -Indopadilla phantoani Hoang et Zhang, sp.n. -is described from the park based on both sexes. This is the second Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Eight species of the genus Phintella were previously recorded from Vietnam (Żabka, 1985, Żabka, 2012, Peng and Xie, 1995, Kanesharatnam & Benjamin, 2019, Hoang et al, 2023. In the present study, 18 species of Phintella (Clade 3) were found.…”
Section: Prediction Of the Species Richness Of Phintella And Phintell...supporting
confidence: 51%
See 1 more Smart Citation
“…Eight species of the genus Phintella were previously recorded from Vietnam (Żabka, 1985, Żabka, 2012, Peng and Xie, 1995, Kanesharatnam & Benjamin, 2019, Hoang et al, 2023. In the present study, 18 species of Phintella (Clade 3) were found.…”
Section: Prediction Of the Species Richness Of Phintella And Phintell...supporting
confidence: 51%
“…In the current classification of Salticidae (World Spider Catalog, 2024), the following eight valid named species of Phintella have been recorded from Vietnam (Kanesharatnam & Benjamin, 2019;Peng & Xie, 1995;Żabka, 1985, 2012: P. accentifera (Simon, 1901); P. aequipeiformis Żabka, 1985;P. argenteola (Simon, 1903); P. bifurcilinea (Bösenberg et Strand, 1906); P. debilis (Thorell, 1891); P. daklak (Hoang et al, 2023); P. suavis (Simon, 1885); and P. vittata (Koch, 1846). A total of 121 Phintella and Phintella-like adult specimens collected in 19 localities of Vietnam, with an additional 43 DNA sequences (32 specimens) from Kanesharatnam and Benjamin (2019), were included as ingroups in our molecular phylogenetic analyses (Table S1; Figures 1 and 2).…”
Section: Target Taxamentioning
confidence: 99%
“…The tropical Asian jumping spider genus Indopadilla Caleb et Sankaran, 2019 is known to be the largest member of the tribe Baviini, accounting for 18 described species [World Spider Catalog, 2024]. To date, only three Indopadilla species have been reported from Vietnam, namely, I. annamita (Simon, 1903), I. cuc Wang, Li et Pham, 2023, and I. phantoani Hoang et Zhang, 2023[Simon, 1903Żabka, 1988;Caleb et al, 2019;Hoang et al, 2023;.…”
Section: Introductionmentioning
confidence: 99%